2017
DOI: 10.1002/cctc.201700904
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus‐Doped and Lattice‐Defective Carbon as Metal‐like Catalyst for the Selective Hydrogenation of Nitroarenes

Abstract: We report carbon can be activated as metal‐like hydrogenation catalyst for the selective hydrogenation of nitroarenes. Using DFT calculations we demonstrated the combination of P dopant and lattice defect in carbon can cause significant electron delocalization and change the band structure to a metal‐like one, and thus both H2 and the nitro group are easily activated for selective hydrogenation. Then we fabricated this carbon catalyst with tunable concentration of P dopant and lattice defects by polymerization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 68 publications
(67 reference statements)
1
45
0
Order By: Relevance
“…The mechanism of optimizing halogenated nitrobenzene hydrogenation reaction by RNC catalyst can be described as follows (Figure ): The halogenated nitrobenzenes and N 2 H 4 ⋅H 2 O in the solution are adsorbed on porous carbon materials. the carbon frameworks of nonmetal heteroatom N are activated and result in the dissociation of surrounding charge, similar to the metal structure of many charges, due to the presence of impurity atoms in the near carbon atom, obvious differences exist at the atomic radius, bond length, and ligand size, thus causing defects at nearby sites were significantly increased . The electronic migration leads to the electron density enrichment around the defect sites; thus, these sites become the active sites for hydrogenation reaction.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of optimizing halogenated nitrobenzene hydrogenation reaction by RNC catalyst can be described as follows (Figure ): The halogenated nitrobenzenes and N 2 H 4 ⋅H 2 O in the solution are adsorbed on porous carbon materials. the carbon frameworks of nonmetal heteroatom N are activated and result in the dissociation of surrounding charge, similar to the metal structure of many charges, due to the presence of impurity atoms in the near carbon atom, obvious differences exist at the atomic radius, bond length, and ligand size, thus causing defects at nearby sites were significantly increased . The electronic migration leads to the electron density enrichment around the defect sites; thus, these sites become the active sites for hydrogenation reaction.…”
Section: Resultsmentioning
confidence: 99%
“…The halogenated anilines were an important group of key intermediates and raw materials in the pharmaceutical industry, such as chlorfluazuron and hexaflumuron. [52][53][54] However, over traditional noble metal catalysts the selective reduction of the halogenated nitro aromatics to the halogenated anilines always made some unwanted dehalogenated side-products which are difficult to separate, seriously reducing the product quality. [55][56][57] The reductions of some representative halogen-substituted nitro aromatics were examined over the Co@CN/SiO 2 -500 catalyst using hydrazine hydrate and the results are given in Table 4.…”
Section: Catalytic Reactionmentioning
confidence: 99%
“…Recent theoretical calculations 38 revealed that different types of oxygen-containing functionalities could change the p electron density of the carbon surface and thus affect the EDA interaction in different degrees. When it comes to phosphorus, the dopants in the carbon matrix acting as electron donors could increase the electron density of carbon 39 and probably promote the EDA interaction as a result. Finally, hydrogen bonding 11,35 and surface reactive adsorption induced by the oxygencontaining groups 36 may also make a contribution to the adsorption of SMX.…”
Section: Adsorption Mechanismmentioning
confidence: 99%
“…S5d †) demonstrated two main signals around 132 and 134 eV, representing phosphorus in the carbon matrix (P-C) and C-O-P functionalities (P-O). 28,39 The relative amount of O-1 and O-2 groups changed aer adsorption. On one hand, extra oxygen introduced through the adsorption of SMX triggered some change.…”
Section: Adsorption Mechanismmentioning
confidence: 99%